PENGARUH MONETARY REWARDS DAN NON-MONETARY REWARDS TERHADAP WORK HAPPINESS YANG DIMEDIASI OLEH WORK ENGAGEMENT PADA KARYAWAN HOTEL DI BANDA ACEH - Lutfi Nur Aslam; Nashrillah Nashrillah (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to measure the effect of monetary rewards and non-monetary rewards on work happiness mediated by work engagement among hotel employees in Banda Aceh City. Data were obtained through a survey of 218 respondents as a sample representing the study population using a questionnaire as a data collection instrument. The sampling technique used is probability sampling with cluster random sampling. Structural Equation Modeling (SEM) is used as an analytical method to determine the effect of the variables involved. The results of the study found that monetary rewards, non-monetary rewards and work engagement have a significant influence on work happiness. The results of the study also found that work engagement was able to mediate the influence of monetary rewards and non-monetary rewards on work happiness.